Communicative english plus - Aquino, Fe O. (Quezon City, 2002)
Communicative english plus is a textbook-workbook designed to develop the lnguistic as well as the communicative competence of freshman college students. Its contents specifically provide students with coprehensive instruction and practice in grammar. The book presents innovative and varied activities that are built around the author's philosophy of languange structure, meaning, and use which are critical components of language learning.
Keywords: English Language- Composition and exercises; English language- grammar